Ex vivo photoactivated chromophore for keratitis-corneal crosslinking on inverted graft: new approach to manage interface infectious keratitis after deep anterior lamellar keratoplasty. Issue 12 (December 2020) - Mularoni, Alessandro; Rania, Laura; Imburgia, Aurelio; Scorcia, Vincenzo; Giannaccare, Giuseppe
Abstract : A 44-year-old man affected by keratoconus underwent deep anterior lamellar keratoplasty (DALK). Two weeks postoperatively, slitlamp examination showed grayish-white lesions in the donor–host interface. Corneal scraping and donor broth culture tested negative for both bacteria and fungi. In vivo confocal microscopy showed elongated particles resembling Candida pseudofilaments. Despite antimicrobial therapy, the clinical picture worsened, and surgical approach was chosen: the graft was peeled off and inverted (epithelium facing down), and ex vivo photoactivated chromophore for infectious keratitis-corneal crosslinking (PACK-CXL) was performed; the recipient bed was washed with antibiotics/antifungals and the graft resutured. Microbiological and histological evaluations of biopsy specimen tested positive for Candida albicans. Postoperative slitlamp examination revealed a progressive recovery of graft transparency with disappearance of the infiltrates. To the authors' knowledge, this is the first report of ex vivo PACK-CXL on inverted DALK graft for the treatment of interface infectious keratitis. This technique allowed the resolution of the infection while sparing the use of new donor tissue.